PENGARUH KADAR AIR DAN SUHU TANAH TERHADAP PENYEBARAN RAYAP TANAH - Agus Ismanto; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
The  result  of  a  study  on  the  effect  of soil moisture  content and  temperature  on subterranean  termite  distribution is presented   in this paper.